Phosphatases control PKA-dependent functional microdomains at the outer mitochondrial membrane - Burdyga, A; Surdo, N; Monterisi, S; Di Benedetto, G; Grisan, F; Penna, E; Pellegrini, L; Bortolozzi, M; Swietach, P; Pozzan, T; Lefkimmiatis, K (National Academy of Sciences, 2018)
Evidence supporting the heterogeneity in cAMP and PKA signaling is rapidly accumulating and has been largely attributed to the localization or activity of adenylate cyclases, phosphodiesterases, and A-kinase–anchoring proteins in different cellular subcompartments. However, little attention has been paid to the possibility that, despite homogeneous cAMP levels, a major heterogeneity in cAMP/PKA signaling could be generated by the spatial distribution of the final terminators of this cascade, i.e., the phosphatases. Using FRET-based sensors to monitor cAMP and PKA-dependent phosphorylation in the cytosol and outer mitochondrial membrane (OMM) of primary rat cardiomyocytes, we demonstrate that comparable cAMP increases in these two compartments evoke higher levels of PKA-dependent phosphorylation in the OMM. This difference is most evident for small, physiological increases of cAMP levels and with both OMM-located probes and endogenous OMM proteins. We demonstrate that this disparity depends on differences in the rates of phosphatase-dependent dephosphorylation of PKA targets in the two compartments. Furthermore, we show that the activity of soluble phosphatases attenuates PKA-driven activation of the cAMP response element-binding protein while concurrently enhancing PKA-dependent mitochondrial elongation. We conclude that phosphatases can sculpt functionally distinct cAMP/PKA domains even in the absence of gradients or microdomains of this messenger. We present a model that accounts for these unexpected results in which the degree of PKA-dependent phosphorylation is dictated by both the subcellular distribution of the phosphatases and the different accessibility of membrane-bound and soluble phosphorylated substrates to the cytosolic enzymes.